HUBUNGAN STIMULASI DENGAN PERKEMBANGAN ANAK USIA 4-5 TAHUN DI DESA KARANGTENGAH KECAMATAN BATURRADEN KABUPATEN BANYUMAS - Sumiyati Sumiyati; Diki Retno Yuliani (Jurnal LINK, 2016)
The main strategies to achieve effective results for the health and survival of children by encouraging breastfeeding, monitoring of child growth and improved communication for behavior change. This study aims to determine the status of development of children aged 4-5 years old in the village Karangtengah Baturraden District of Banyumas. Conducted an observational study with cross sectional design, with independent variables: the stimulation provided the mother and the dependent variable: the development of children aged 4-5 years. Measuring tool using instruments KPSP to 41 children and gave questionnaires to 41 mothers in September to October 2015. Data were analyzed using chi square test. The results showed a picture capabilities gross motor development and fine motor skills according to developmental age 4-5 years, children aged 4-5 years as many as 33 children (80.5%) have the ability to date, and as many as 8 children (19.5%) experienced developmental disorders, there is a significant association between stimulating the development of children aged 4-5 years with  p=0.000. Based on this study suggested the family needs to increase stimulation, especially aspects of speech-language-independence and socialization ability to stimulate children's development, health education needs to be done to mothers of stimulation to stimulate the child's basic abilities